2018
DOI: 10.1038/s41598-017-17913-x
|View full text |Cite|
|
Sign up to set email alerts
|

LSD1 activation promotes inducible EMT programs and modulates the tumour microenvironment in breast cancer

Abstract: Complex regulatory networks control epithelial-to-mesenchymal transition (EMT) but the underlying epigenetic control is poorly understood. Lysine-specific demethylase 1 (LSD1) is a key histone demethylase that alters the epigenetic landscape. Here we explored the role of LSD1 in global epigenetic regulation of EMT, cancer stem cells (CSCs), the tumour microenvironment, and therapeutic resistance in breast cancer. LSD1 induced pan-genomic gene expression in networks implicated in EMT and selectively elicits gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
134
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(149 citation statements)
references
References 70 publications
10
134
1
Order By: Relevance
“…Boulding et al showed that CTCs from metastatic breast cancer patients express high levels of LSD1. They observed that EMT can be suppressed using chemical LSD1 blockers, concluding that LSD1 plays a role in EMT and metastasis initiation …”
Section: Liquid Biopsy Componentsmentioning
confidence: 99%
“…Boulding et al showed that CTCs from metastatic breast cancer patients express high levels of LSD1. They observed that EMT can be suppressed using chemical LSD1 blockers, concluding that LSD1 plays a role in EMT and metastasis initiation …”
Section: Liquid Biopsy Componentsmentioning
confidence: 99%
“…High LSD1 levels are seen during EMT in MCF‐7 breast cancer cells following stimulation with Phorbol 12‐myristate‐13‐acetate/TGF‐β and in fully dedifferentiated mesenchymal MDA‐MB‐231 breast cancer cells. Decreased LSD1 levels have also been reported during the opposing biological process, mesenchymal‐epithelial transition …”
Section: Epigeneticsmentioning
confidence: 96%
“…Boulding et al showed that treatment of induced MCF‐7 cells with LSD1 siRNA completely abolished the CD44 + /CD24 − CSC population, and pharmacological inhibition with a known LSD1 inhibitor pargyline partially inhibited CSC formation. In addition, LSD1 inhibition reduced EMT and stemness‐like resistance signatures induced by chemotherapy . In vivo inhibition of LSD1 in combination with chemotherapy reduced tumor growth compared to chemotherapy alone.…”
Section: Epigeneticsmentioning
confidence: 99%
See 2 more Smart Citations